Why did they comply? External incentive model, role-playing and socialization in the alignment of sanctions against Russia in Albania and Montenegro. Issue 8 (17th November 2021) - Marošková, Tereza; Spurná, Karolína
ABSTRACT: This paper analyses the Europeanization of the foreign policies of the Western Balkans states, using the examples of the Montenegrin and Albanian alignment with the EU sanctions against Russia. Using the Process-tracing method we discover that the role-playing mechanism in the case of Montenegro and socialization in Albania's case are behind the alignment in sanctions. Despite the EU's potential leverage, the external incentive model (EIM) is almost completely absent. This is rather unexpected given EIM's prevalence in other policy areas. This suggests that the EU might be treating the foreign policy area differently to other enlargement chapters, reflecting the special position of the Common Foreign and Security Policy (CFSP) as an intergovernmental policy with no adaptational pressure at the EU level.